Hubungan antara Job Insecurity dengan Burnout pada Karyawan Outsourching Fifgroup Cabang Padang - Asroni Rasip; Harri Kurniawan; Isna Asyri Syahrina (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to determine the relationship between job insecurity with burnout on FIFGROUP Padang outsourching employees. The independent variable in this study is job insecurity and the dependent variable is burnout. The measuringinstrument used in this study uses a saturated sample technique. The sample in this study was 40 employees of FIFGROUPoutsourching Padang branch. The validity and reliability test in this study uses the Cronbach Alpha technique. The results ofthe validity coefficient on the job insecurity scale move from rix = 0.305 to rix = 0.706 with a reliability coefficient of α =0.884. While on the burnout scale move from rix = 0.373 to rix = 0.737 with a reliability coefficient of α = 0.915 Based ondata analysis, obtained correlation value of 0.406 with a significance level of 0.009 which means the hypothesis is accepted.This shows that there is a significant relationship between job insecurity with burnout on Padang branch FIFGROUPoutsourching employees.